Helsinki Airport and Tower ... - Campbell, Sandy (University of Alberta Library, 2018)
View of the Helsinki Airport and tower from the tarmac. The buildings are primarily white or silver metallic colours with aqua coloured glass. Jetways for gates 21 and 22 are visible, along with baggage equipment and several vehicles. ...